(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2017)
Meadow vegetation of floodplain complex in Kyiv city are presented by 2 classes, 5 orders, 10 alliances and 25 associations. The most cenotical diversity belongs to Molinio- Arrhenatheretea. The phytocenosis of associations Poo palustris-Alopecuretum pratensis, Trifolio-Festucetum rubrae, Koelerio-Agrostietum vinealis are most widely represented, they have 44,92 % of all our releves from phytocenosis. Species diversity of phytocenosis of Pragmiti-Magno-Caricetea are much less presented than Molinio-Arrhenatheretea communities. Iris sibirica, rare species from Red book of Ukraine, was found in 7 associations. These asociations are Agrostio vinealis-Calamagrostietum epigei, Festucetum pratensis, Koelerio-Agrostietum vinealis, Lysimachio vulgaris-Filipenduletum, Agrostio giganteae-Festucetum pratensis, Poetum pratensis, Poo palustris-Alopecuretum pratensis.